ACADEMIC SUPERVISION OF MADRASAH PRINCIPALS IN IMPROVING THE QUALITY OF LEARNING - Muhammad Al Khawarizmi Harahap (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research is motivated by the importance of academic supervision by madrasah principals in improving the quality of learning. The purpose of this study is to examine the concept and role of academic supervision by madrasah principals in improving the quality of learning in madrasahs, as well as to analyze the impact of academic supervision on improving the quality of learning and the quality of madrasahs as a whole. This study uses a library research method with a qualitative approach. Data collection techniques are carried out through documentation by reviewing various written sources such as books, journals, and scientific articles relevant to the research topic. Data analysis techniques use content analysis, namely by systematically identifying, categorizing, and interpreting the content of the data to gain a deep understanding. The results of the study indicate that academic supervision by madrasah principals plays a significant role in improving the quality of learning through directed planning, systematic implementation, and follow-up in the form of continuous coaching and evaluation. Thus, academic supervision is one of the strategic factors in improving teacher professionalism and the quality of learning.